National integration and communal harmony - National Seminar on "National integration and Communal Harmony in India (2002: Punjab University); Baltej Singh Mann; Punjabi University : Pub. Bureau (Patiala : Publication Bureau, Punjabi University, 2004)
Contributed articles presented at the National Seminar on " National Integration and Communal Harmony" held in National Foundation for Communal Harmony in India" at the Punjabi University, Patiala on Oct. 2002
Includes index
Bibliography: p. 296-333
Keywords: Nationalism -- India -- Congresses; Communalism -- India -- Congresses; India -- Ethnic relation -- Congresses